(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of syntax and its central role in the structure of sentences. It provides a detailed analysis of the main units of syntax—words, phrases, clauses, and sentences—and their interrelationship in forming grammatically correct structures. The piece contrasts two major approaches to syntax: traditional, rule-based approaches, such as generative grammar, and cognitive approaches, which focus on the relationship between language and human cognition. The article delves into how traditional theories, particularly those developed by Noam Chomsky, rely on formal rules and hierarchical structures to explain sentence formation. It also examines cognitive approaches like cognitive grammar and construction grammar, which view syntax as a product of mental representations and conceptual structures. The comparison highlights the differences between formal, abstract rule-based models and those that emphasize meaning and human cognition in syntactic analysis. The article concludes by acknowledging the value of both perspectives in advancing our understanding of syntax, suggesting that a synthesis of the two can provide a more comprehensive view of how language functions.